THE COURSE OF DISSECTING ANEURYSM OF THE AORTA - N. A. Kosheleva; E. A. Gorokhova; M. S. Rezepkinа (SINAPS LLC, 2016)
Research objective. To define features of a course of dissecting aortic aneurysm now.Materials and methods. 11 clinical records of the patients with the established diagnosis of dissecting aortic aneurysm who have come to Regional clinical hospital of Saratov for 2015 are analysed.Results. Along with traditional risk factors, such as the male, existence of arterial hypertension are revealed also additional risk factors, in particular, regular heavy lifting. Gender features in localization of dissecting aortic aneurysm are defined: at men more often of dissecting aortic aneurysm of an aorta is localized in the abdominal aorta, at women in the thoracic region.Conclusions. Additional risk factor of stratification of dissecting aortic aneurysm in the thoracic region at women is the systematic raising of weights.